2020
DOI: 10.3390/biology9030049
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Formulation of Chlorpyrifos Alters Neurological Behaviors and Fertility

Abstract: Pesticides are known to result in toxic insult. We aimed to evaluate Judo 40, the commercial formulation of chlorpyrifos on the neurological activities, fertility, and hormone levels of male rats. Male Wistar rats were treated orally with 1 mL of 20 or 50 mg/kg Judo 40. The doses were administered four times, twice a day. Sexual and exploratory behavior indices, fertility indices, serum androgen levels, blood acetylcholinesterase (BChE) levels, and neurological and muscular effects were evaluated. Serum testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In the current experiment, IPD and/or CPS-exposed rats showed notable reduced locomotion and exploration in the OFT. In this regard, Kudavidanage, et al [ 62 ] confirmed that oral CPS dosing impaired coordination and decreased muscle strength in rats. On the other hand, AChE inhibition has been reported to disrupt motor function [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, IPD and/or CPS-exposed rats showed notable reduced locomotion and exploration in the OFT. In this regard, Kudavidanage, et al [ 62 ] confirmed that oral CPS dosing impaired coordination and decreased muscle strength in rats. On the other hand, AChE inhibition has been reported to disrupt motor function [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in litter size as an indicator of pesticide vulnerability is attributed to diverse causes, such as Ch and Cy capacity to cross the placental barrier (Rager et al, 2020). The Ch (Kudavidanage et al, 2020) and Cy (Assayed et al, 2010) exposures promoted pre-implantation losses. Oxidation damage to fallopian tubes and increased apoptotic damage to embryos by the pesticide mixture are also incriminated (Guney et al, 2007;Talbot and Riveles, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This, however, does not rule out the possibility of low testosterone in veterans with Gulf War Illness compared to sedentary Gulf War-era veteran controls. Several studies in rats have identified anti-androgenic effects (i.e., reduced levels of testosterone, follicle-stimulating hormone, and luteinizing hormone, as well as testicular shrinkage) of the GW-relevant organophosphate acetylcholinesterase inhibitor and pesticide, chlorpyrifos [77][78][79][80][81]. Studies investigating the diffuse chronic pain of fibromyalgia, which has commonalities with other chronic pain conditions such as PTSD and Gulf War Illness, have suggested low or deficient testosterone serum levels that likely cause an inflamed nociceptive nervous system [82].…”
Section: Discussionmentioning
confidence: 99%